METHODOLOGICAL CONTENT OF IMPROVING THE INFORMATION- METHODICAL COMPETENCE OF A CHEMISTRY TEACHER IN A DIGITAL EDUCATIONAL ENVIRONMENT - Khudayor Rajabov (The Bioscan, 2024)
The article involves the methodological content of improving information and methodological competence in a digital educational environment and, on its basis, develops an organizational and didactic model for the development of information and methodological competence of a future chemistry teacher. The functions and principles of the process management system for increasing the information and methodological competence of future chemistry teachers are described.